Answer:
901$
Step-by-step explanation:
Answer:
m = (g - 5) / (a + 3)
Step-by-step explanation:
g-3m=am+5
- Get all the m's on one side.
g - 5 = am + 3m
- Combine the m's into one term, using brackets
g - 5 = (a + 3)m
- Get m on it's own by dividing by a + 3
(g - 5) / (a + 3) = m
We can write this in math as x+y+z=104, x=y-6, and z=3y
Because we already know what x and z are in terms of y, we can substitute our values for x and z into the first equation. This now looks like (y-6) + y + (3y) = 104. Now we can simplify our equation to find our value for y.
y-6 + y + 3y = 104 simplifies to 5y - 6 = 104, then 5y=110, and finally y=22.
Now that we know our value for y we can find our values for x and z by substituting our value for y into the other two equations.
The second equation x = y-6 can be simplified as x = 22 - 6 and further simplified as x = 16.
The third equation z = 3y can be written as z = 3(22) or z = 66.
Our three numbers are 16, 22, and 66. Hope this helps you!
Answer:
The answer is - 113 that is the correct answer skipping in three's and the first one is - 97
The answer is 31.832142857.